FINGER PAINTING DALAM MENSTIMULASI KECERDASAN JAMAK PADA ANAK USIA 3-4 TAHUN (Studi Kualitatif di KB-TK Batik PPIP Pekalongan) - Oktarina Dwi Handayani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
This study aims to determine the substance of the main activity of finger painting in the age of 3-4 years. This study used a descriptive qualitative research method with an analysis of the technical flow model proposed by Miles and Hubberman. The location of this study is at the PPIP TK TK-Pekalongan. The subjects in this research activity were educators and students who conducted 3-4 years at the institution. Data collection is done by using interviews, and documenting. From the results of the research that has been done, the results show that the main activity of finger painting can develop intelligence in children for 3-4 years, namely in aspects; Mathematical, kinesthetic, visual, spatial, linguistic, interpersonal and intrapersonal aspects of Logic Mathematics.